Neurodevelopmental outcomes at 2 and 5 years of age in very-low-birth-weight preterm infants born between 2002 and 2009: A prospective cohort study in Taiwan - Chia-Ying Lin; Chyong-Hsin Hsu; Jui-Hsing Chang (Elsevier, 2020)
Background: Neurodevelopmental outcome in preterm infants has been of great importance in recent decades. We determined the prevalence of abnormal neurodevelopmental outcomes and associated risk factors of very-low-birth-weight (VLBW) preterm infants at 2 and 5 years of age. Methods: We conducted a population-based, prospective cohort study of VLBW preterm infants born between 2002 and 2009 in Taiwan. Sociodemographic, neonatal data, and neurological assessments at 2 and 5 years of age were obtained from the database of Taiwan Premature Infant Follow-up Network. Results: Of the 6549 VLBW preterm infants included in the study, 5407 (82.56%) survived to discharge; 4105 and 1427 participated in follow-up assessments at age 2 and 5 years, respectively. At age 5 years, 76.87% (1097/1427), 12.05% (172/1427), and 8.76% (125/1427) of children had normal, borderline, and abnormal neurocognitive outcomes, separately. Among the enrolled children, 1385 were followed at both 2-year and 5-year-old. Among the 233 children with abnormal neurodevelopmental outcomes at age 5 years, nearly one-fifth (18.03%, 42/233) had normal or borderline neurodevelopmental outcomes at age 2 years. Among the 154 children with borderline neurodevelopmental outcomes at age 5 years, 71.43% (110/154) had normal or borderline neurodevelopmental outcomes at age 2 years. The risk factors significantly associated with disadvantageous (worsening or remaining unimproved) neurodevelopmental outcomes were lower gestational age, cystic periventricular leukomalacia, and paternal or maternal education ≤12 years. Conclusion: Almost one-fifth of VLBW preterm children with abnormal neurodevelopmental outcomes at age 5 years had normal or borderline neurologic and developmental assessments at age 2 years. For the high risk group such as VLBW preterm children, serial follow-up assessments beyond 2 years of age may be warranted and the eligibility of early intervention service should be revised by the government so proper and targeted intervention can be implemented at earlier age. Key Words: children development, preterm infants, risk factors, very-low-birth-weight infant